Analysis of sleep deprivation-associated Homer1 gene and protein acting on synaptic plasticity by bioinformatics and animal experiments - Li, Yun; Zhao, Lina; Zhou, Qi; Zhang, Xizhe; Song, Jiannan; Wang, Xinyi; Yang, Chenyi; Wang, Haiyun (ANESTHESIOLOGY AND PERIOPERATIVE SCIENCE, 2023)
Background Homer1, an immediate early gene, is related to sleep deprivation (SD), and its protein products are involved in synaptic plasticity affecting the cognitive process. This study aimed to identify the SD-associated key Homer1 gene in the brain and explore the value of Homer1 proteins acting on synaptic plasticity in SD. Methods GSE9441 was extracted from Gene Expression Omnibus (GEO) database. Differentially expressed genes (DEGs) between SD and Control samples were achieved by R software and were analyzed by the Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway, and gene set enrichment analysis (GSEA). Protein–protein interactions (PPI) network was built by the GeneMANIA databases. In animal experiments, male C57BL/6 J mice (aged 12–13 weeks) were sleep deprived for 6 h, followed by independent behavioral tests and in vitro assays. Morris water maze (MWM) was used to evaluate learning and memory function. The expression of hippocampal Homer1 proteins was detected by Western blot analysis and its distribution in CA1 by immunohistochemistry and immunofluorescence staining. Synaptic plasticity was assessed by Golgi staining and long-term potentiation (LTP) testing in the hippocampal CA1 region. Results Homer1 was the hub gene most associated with SD, and its protein products specifically acted on the regulation of synaptic plasticity in bioinformatics. SD mice exhibited spatial memory impairment accompanied by increased Homer1a expression in hippocampal tissue and CA1 region. SD did not induce Homer1b/c overexpression of mice in the hippocampus. SD impaired the hippocampal synaptic plasticity of mice by reducing the density of dendritic spines and inhibiting LTP in the hippocampal CA1 region, which may involve the overexpression of Homer1a in the hippocampus. Conclusion Homer1 gene is a core brain molecule associated with acute SD, and its protein product Homer1a is involved in the changes in cognitive brain function following short-term SD, especially the impact on hippocampal synaptic plasticity.